ALTERNATIF BANGUNAN AIR UNTUK PENYEDIAAN AIR BAKU DI PULAU GILI-GILI, NUSA TENGGARA BARAT - Affandi, Diah (Jurnal Air Indonesia, 2010)
In order to meet water needs during the dry season in West Nusa Tenggara (NTB), particularly on small islands in the NTB area needed a facility that can accommodate the rain water in the rainy season, so water supply can be used during the dry season. Characteristics of land in coastal areas in particular, other than flat land also contains sand, so the soil tends to have relatively high permeabilities. To build waterworks facilities suitable to local conditions then, required an assessment of alternative types of water structure adapted to the geological conditions and availability of building materials to be used.Ã‚Â Keywords : Karakteristik Tanah, Alternative Bangunan Air